A COMPARATIVE ANALYSIS OF DISCRETE AND BATCH PICKING AND THE IDENTIFICATION OF FACTORS INFLUENCING ORDER PICKING EFFICIENCY - Oh, Seung-Chul; Min, Hokey; Ahn, Young-Hyo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
In a typical warehouse environment, order picking represents one of the highest prioritized activities due to its impact on warehousing productivity, operating costs, and order fulfillment. Order picking generally involves determining a sequence of visitations with inventory locations where the ordered items are stored and then retrieved with the assurance of correct product specifications and quantity according to the customer order. In the era of e-commerce, order picking has become highly labor-intensive and contributed to warehouse productivity declines due to the increased piece-by-piece picks. To mitigate the adverse impact of inefficient, unorganized order picking, we employed the alternative batch picking method and then compared its efficiency to that of a conventional discrete order picking method. This paper validated the usefulness of the proposed method by its application to order picking problems encountering the Korean processed food manufacturer. Based on a series of simulation experiments with actual data, we verified the comparative efficiency of batch picking and identified a couple of key factors affecting order picking efficiency.